Functional recoding of Chlamydomonas reinhardtii thioredoxin type-h into photosynthetic type-f by switching selectivity determinants - Lemaire, Stéphane D.; Lombardi, Gianluca; Mancini, Andrea; Carbone, Alessandra; Henri, Julien (Frontiers in Plant Science, 2025)
Thioredoxins are ubiquitous disulfide reductases folded as an α/β domain of 100-120 amino acid residues. Functional redox site is composed of a pair of cysteines in a canonical WCGPC pentapeptide exposed at the surface of thioredoxins, that reduces disulfide bonds on target proteins. Several genetic isoforms of thioredoxins are phylogenetically classified into seven types, including type-h involved in general functions in the cytosol and type-f specifically associated to photosynthetic functions in chloroplasts. Specialization of thioredoxin function is correlated to its selectivity towards a type-dependent repertoire of protein targets. In this study, we combined biochemical and computational approaches to identify amino acid residues of photosynthetic type-f thioredoxin contributing to target the Calvin-Benson-Bassham cycle enzymes fructose-1,6-bisphosphatase and sedoheptulose-1,7-bisphosphatase. By introducing these residues into the scaffold of type-h thioredoxin, we generated a synthetic chimera of thioredoxin-h active towards photosynthetic fructose-1,6-bisphosphatase in vitro. Our combined computational and experimental approach provides a general pipeline for the design of molecular switches, enabling precise functional control.